2020
DOI: 10.1021/acsomega.0c03352
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Biaryl Cyclic Lipopeptides Derived from Arylomycins

Abstract: An efficient approach for the solid-phase synthesis of N-methylated tailed biaryl cyclic lipopeptides based on the structure of arylomycins was established. Each of these analogues incorporates an N-terminal linear lipopeptide attached to a biaryl cyclic tripeptide containing a Phe–Tyr, a Tyr–Tyr, or a His–Tyr linkage. This methodology first involved an intramolecular Suzuki–Miyaura arylation of a linear peptidyl resin incorporating the corresponding halogenated amino acid at the N-terminus and a boronotyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In order to build on their previous work employing MW-assisted Suzuki–Miyaura macrocyclization reaction [ 111 ], in 2020, Ng-Choi et al reported the MW-assisted synthesis of biaryl cyclopeptides via on-resin intramolecular Suzuki–Miyaura coupling [ 112 ]. Suzuki–Miyaura macrocyclization of 113 was performed on solid-support using Pd 2 (dba) 3 (0.2 eq), SPhos (0.4 eq), and KF (4 eq) in DME/EtOH/H 2 O (9/9/2) at 120 or 140 °C under MW irradiation for 30 min, followed by simultaneous resin cleavage and side-chain deprotections in TFA/TIS/H 2 O to provide 114 ( Scheme 33 ).…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to build on their previous work employing MW-assisted Suzuki–Miyaura macrocyclization reaction [ 111 ], in 2020, Ng-Choi et al reported the MW-assisted synthesis of biaryl cyclopeptides via on-resin intramolecular Suzuki–Miyaura coupling [ 112 ]. Suzuki–Miyaura macrocyclization of 113 was performed on solid-support using Pd 2 (dba) 3 (0.2 eq), SPhos (0.4 eq), and KF (4 eq) in DME/EtOH/H 2 O (9/9/2) at 120 or 140 °C under MW irradiation for 30 min, followed by simultaneous resin cleavage and side-chain deprotections in TFA/TIS/H 2 O to provide 114 ( Scheme 33 ).…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%
“…Suzuki–Miyaura macrocyclization of 113 was performed on solid-support using Pd 2 (dba) 3 (0.2 eq), SPhos (0.4 eq), and KF (4 eq) in DME/EtOH/H 2 O (9/9/2) at 120 or 140 °C under MW irradiation for 30 min, followed by simultaneous resin cleavage and side-chain deprotections in TFA/TIS/H 2 O to provide 114 ( Scheme 33 ). By using this developed methodology, several other analogs, including cyclolipopeptides 115 and 116, were synthesized [ 112 ].…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%
“…The approach was finally applied to the solid‐phase synthesis of N ‐methylated tailed biaryl cyclic lipopeptides based on the structure of arylomycins [40] . Arylomycins are natural products that have shown very interesting antibacterial activity.…”
Section: Classical Pd‐catalyzed Reactions In Solid Phasementioning
confidence: 99%
“…The approach was finally applied to the solid-phase synthesis of N-methylated tailed biaryl cyclic lipopeptides based on the structure of arylomycins. [40] Arylomycins are natural products that have shown very interesting antibacterial activity. The key reaction was the cyclization of supported peptides 54-56, catalyzed by Pd 2 (dba) 3 and SPhos as ligands, to give the intermediates 57-59.…”
Section: Suzuki-miyaura Reactionmentioning
confidence: 99%
“…1b). 4,5 More recently, a novel PCSK9 inhibitor produced by Merck contains a peptide bridge involving a heterobiaryl linkage between a triazole and an aryl ring. Synthetically, heterobiaryl and biaryl linkages in peptide macrocycles are typically constructed from building blocks and then incorporated into the peptide backbone via a conventional amidation reaction.…”
Section: Introductionmentioning
confidence: 99%